Die Religionswissenschaft und das Christentum, Eine historische Untersuchung über das Verhältnis von Religionswissenschaft und Theologie. - Hjelde (Numen Book Series, 1993)
What are religious studies? What is theology? And what is their relationship to each other? In the light of such theoretical and methodological questions this historical inquiry asks what characterizes the study of Christianity within comparative religion-as distinguished from that of Christian theology? In the three main sections of the book representative texts from the history of comparative religion-including Schleiermacher and some other theological forerunners in the 19th century-are analyzed from a methodological and a material point of view. On this basis an answer is sought to the following questions: What has been the place of the study of Christianity within this discipline? On which methodological principles has it been based? And what kind of picture of Christianity has it presented?